Optimalisasi Infrastruktur Jaringan Internet Desa untuk Mendukung Digitalisasi UMKM dan Pendidikan - Willy Prihartono; Yudhistira Arie Wijaya; Aliya Anisa Rahma; Irma Agustina (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Digital transformation is a crucial element in improving the quality of education and developing Micro, Small and Medium Enterprises (MSMEs), especially in rural areas. However, limited internet network infrastructure is a major challenge that must be overcome. This research aims to identify problems and propose strategies for optimizing village internet networks to support the digitalization of the education sector and MSMEs. The method used was direct observation in Ketapanrame Village, Trawas District, Mojokerto Regency, as well as a literature study approach to network technology solutions. The results showed that although the availability of internet networks already exists, the quality and equity of access is still low. Therefore, it is necessary to strengthen the infrastructure through increasing bandwidth, placing strategic access points, and utilizing technologies such as wireless mesh networks (WMN). In addition, community empowerment through digital literacy training is also very important to ensure optimal utilization of the available infrastructure. The implementation of this strategy is expected to encourage the improvement of the quality of digital-based learning and expand the MSME market through online platforms. Optimizing village internet networks is not only about technical aspects, but also includes strengthening human resource capacity and local government policy support. Thus, the digitization of education and MSMEs can be an important pillar in the economic and social development of villages.